Prática pedagógica docente na perspectiva de uma estudante com deficiência múltipla - SARMENTO, Giselle Fonseca (2024)
This article aims to analyze the pedagogical practices of teachers working with a student with multiple disabilities. For this, using as basis authors mantoan (2002, 2011); Vygotsky (1991); Ross (2012); Masini (2011); Among others. The field research was conducted in the E.E.E.F.M. professor gasparino batista da silva-sede, along with participant observation in the regular classroom, aiming to understand the role of the school and the family in the formation of students. We conclude that the relationship between school and family are fundamental to student learning, the continuing education of teachers has to happen so that education professionals improve their teaching practices, and work increasingly better with students with multiple disabilities.